International policy, recommendations, actions and mitigation efforts of anthropogenic underwater noise. (1st March 2021) - Chou, Emily; Southall, Brandon L.; Robards, Martin; Rosenbaum, Howard C.
Abstract: Anthropogenic underwater noise levels have generally increased as industrial activities in the ocean have become more prevalent. Because of the central nature of sound in the lives of many marine animals, and the known and potential adverse impacts of noise, it is also gaining increased international recognition as an important global conservation issue. Here, a current compilation and synthesis of official documents, reports, and strategic plans from various intergovernmental, governmental, and international organizations, and noise-related projects and programs, demonstrate increasing efforts to understand anthropogenic underwater noise, and the mitigation and management measures that are being considered to reduce noise. While some entities aim to better understand and quantify underwater noise and its impacts, others have recommended explicit mitigation measures including spatio-temporal approaches to managing noise sources, and vessel quieting technologies. New approaches also include the development of certification or voluntary noise-reduction programs and agreements. We highlight four considerations that will better link the potential impacts of noise with corresponding mitigation and noise reducing efforts: 1) collaboration to address the transboundary and cumulative nature of underwater noise; 2) differing countries' implementation capabilities for addressing noise; 3) time and intensity tradeoffs (e.g., louder noise for a shorter time period versus quieter but for longer); and 4) variable noise impacts depending on specific life history stages and life functions. Our review affirms the international consensus that anthropogenic underwater noise is a currently pervasive yet relatively transient form of pollution, the effects of which can be significantly reduced through effective mitigation and regulatory action. Highlights: Anthropogenic underwater noise is transboundary and can adversely impact ocean life. This internationally recognized issue calls for partnership, mitigation and policy. Recommend use of spatio-temporal mitigation, quieting technology and best practices. Need for urgent research and action to implement effective noise reduction measures. We suggest key areas for future action to better address noise impacts in the ocean.